Cold cold bones - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series, 2022)
"#1 New York Times bestselling thriller writer Kathy Reichs returns with her twenty-first novel of suspense featuring forensic anthropologist Temperance Brennan who, after receiving a box containing a human eyeball, uncovers a series of gruesome killings eerily reenacting the most shocking of her prior cases."--